2022
DOI: 10.1111/jora.12744
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Parental Phubbing and Short‐Form Videos Addiction Among Chinese Adolescents

Abstract: Phubbing" is a new term that is used to define an act of neglecting an individual's companion/s in a daily social context to focus on that individual's smartphone. This study explored the relationship between parental phubbing (PP) and adolescent short-form videos addiction (SFVA), and the mediating role of relative deprivation (RD) and the moderating role of peer communication (PC) in this relationship. A total of 549 high-school students from Northern China voluntarily participated in the survey. The direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 84 publications
(92 reference statements)
0
21
1
Order By: Relevance
“…An empirical study of university students showed that peer phubbing could cause social media reliance (Chu et al 2021). Although many previous studies have substantiated that parental phubbing can lead to teenagers' internet dependence (Xie et al, 2019, Zhang, Ding & Wang, 2021, smartphone reliance (Zhao, Ye, Luo & Yu, 2022), short-form video addiction (Wang & Lei, 2022) and PSNU (Hong et al, 2019), there is no proof of the association between parental phubbing and PSNU. Based on the past findings, our team posited the following.…”
Section: Parental Phubbing and Psnumentioning
confidence: 99%
“…An empirical study of university students showed that peer phubbing could cause social media reliance (Chu et al 2021). Although many previous studies have substantiated that parental phubbing can lead to teenagers' internet dependence (Xie et al, 2019, Zhang, Ding & Wang, 2021, smartphone reliance (Zhao, Ye, Luo & Yu, 2022), short-form video addiction (Wang & Lei, 2022) and PSNU (Hong et al, 2019), there is no proof of the association between parental phubbing and PSNU. Based on the past findings, our team posited the following.…”
Section: Parental Phubbing and Psnumentioning
confidence: 99%
“…For example, TikTok has 486 million monthly active users, and approximately 22 percent watch videos for more than 1 h per day [ 4 , 5 ]. This is especially true for adolescents due to their immature self-control abilities, along with the pursuit of psychological needs [ 6 ]. Excessive use may lead to a series of negative problems, such as increased depression and loneliness, distraction, low sleep quality, and social isolation [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Parental phubbing refers to a parent’s act of snubbing their children in daily parent–child conversations or in daily time by focusing on a mobile phone [ 33 ]. On the one hand, during a parent–child conversation, parental phubbing behavior may distance the intimate relationship with their children and make them feel they are excluded [ 6 ]. From the children’s perspective, they perceive that mobile phones are more vital than they are [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations